Sexual and Gender-Based Violence Among Refugees and Internally Displaced Persons in the Democratic Republic of the Congo: Post-Conflict Scenario - Lugova H; Samad N; Haque M (Risk Management and Healthcare Policy, 2020)
Halyna Lugova,1 Nandeeta Samad,2 Mainul Haque3 1Unit of Community Medicine, Faculty of Medicine and Defence Health, National Defence University of Malaysia, Kuala Lumpur, Malaysia; 2Department of Public Health, North South University, Dhaka, Bangladesh; 3Unit of Pharmacology, Faculty of Medicine and Defence Health, National Defence University of Malaysia, Kuala Lumpur, MalaysiaCorrespondence: Mainul HaqueFaculty of Medicine and Defence Health, National Defence University of Malaysia, Kem Perdana Sugai Besi, Kuala Lumpur 57000, MalaysiaTel +60109265543Email runurono@gmail.comAbstract: The ongoing humanitarian crisis in the Democratic Republic of the Congo has triggered sexual and gender-based violence, including rape, sexual slavery, trafficking, intimate partner violence, and sexual exploitation. Gender inequalities and abuse of power experienced by women and young girls at refugee settings further exacerbate their vulnerability to different forms of violence. This study aimed to offer an evidence-based approach to developing strategies in tackling the complex problem of sexual and gender-based violence among refugees and internally displaced persons in the Congo. We conducted a narrative review of all the relevant papers known to the authors to explore the origins of the problem, its implications on public health, and its impact on equity. The study revealed that sexual assault survivors face physical and psychological sufferings, excruciating emotions, and profound disruption of their social well-being since they are often stigmatized and ostracized by society. The analysis of current government policies revealed a lack of programs to address survivors’ specific concerns and policy enforcement problems. This study suggested strategic objectives and policy implementation steps. The proposed strategies address women empowerment and gender stigma, provision of effective health services, and adequate response action.Keywords: SGBV, evacuees, post-conflict, policy, DRC